Integrative neuromuscular training enhances physical fitness in 6- to 14-year-old rugby players - Alonso-Aubin, D. A.; Picón-Martínez, M.; Rebullido, T. R.; Faigenbaum, A. D.; Cortell-Tormo, J. M.; Chulvi-Medrano, I. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to assess the effects of an 8-week integrative neuromuscular training (INT) program on physical fitness measures in young rugby players. A sample of 138 male rugby players (age range, 6-14 years) was divided into 5 age-related groups: group 1 (G1) (n = 20; age, 7.05 ± 0.58), group 2 (G2) (n = 27; age, 8.57 ± 0.49), group 3 (G3) (n = 31; age, 11.02 ± 0.56), group 4 (G4) (n = 33; age, 13.12 ± 0.58, and group 5 (G5) (n = 27; age, 14.85 ± 1.53 and additionally into 2 game position groups: forwards (FOR) (n = 69) and backs (BAC) (n = 69). Physical fitness measures included the Functional Movement Screen (FMS), dominant and nondominant hand-to-eye coordination, sprint capacity, core muscular endurance, and lower- and upper-body power. Integrative neuromuscular training (INT) included progressive strength, coordination, and speed exercises performed twice per week for 20 minutes. Following INT, significant improvements in selected age-related groups (p < 0.01) were found in total FMS score G3 (effect size [ES] = 0.47), G4 (ES = 0.88), and G5 (ES = 0.58); dominant hand-to-eye coordination G1 (ES = 1.48), G2 (ES = 0.71), G3 (ES = 0.55), G4 (ES = 1.47), and G5 (ES = 1.15), nondominant hand-to-eye coordination G2 (ES = 0.74), G4 (ES = 1.34), and G5 (ES = 1.09); lower-body power G2 (ES = 0.44), G4 (ES = 0.39), and G5 (ES = 0.43); core muscular endurance G1 (ES = 0.82), G3 (ES = 0.68), and G4 (ES = 1.04); upper-body power G2 (ES = 0.53); and sprint capacity G4 (ES = 0.69). Significant improvements were also found between player's positions for all tests. These findings indicate that a progressive INT program can enhance functional movement abilities and selected physical fitness measures in young rugby players regardless of game position and age.